2018
DOI: 10.1177/1524839918786234
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Health Education Competencies Among Obesity Prevention and Nutrition Education Professionals

Abstract: The study purpose was to examine perceived health education competencies among those responsible for planning, implementing, and evaluating health education programs. A total of 172 obesity prevention and nutrition education professionals in the United States completed a survey measuring their perceived competency to plan, implement, and evaluate nutrition education/obesity prevention education programs based on the National Commission for Health Education Credentialing health education competencies and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…They did not use the proper weight loss methods; they did not know the basics of diet and had poor nutritional knowledge. Although the various studies in the field of obesity showed that having a proper diet, 64,65 interventions, and standard programs to prevent obesity 66,67 and nutritional training 68,69 reduced weight and prevent obesity. But what this study adds to the previous studies is that if people in a society do not have a proper understanding of nutrition and obesity, they cannot plan properly to prevent it or find suitable ways to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…They did not use the proper weight loss methods; they did not know the basics of diet and had poor nutritional knowledge. Although the various studies in the field of obesity showed that having a proper diet, 64,65 interventions, and standard programs to prevent obesity 66,67 and nutritional training 68,69 reduced weight and prevent obesity. But what this study adds to the previous studies is that if people in a society do not have a proper understanding of nutrition and obesity, they cannot plan properly to prevent it or find suitable ways to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Public health issues which health educators are engaged include the decades-long opioid and obesity epidemics, as well as more rapidly proliferating events such as bioterrorism events and infectious diseases, such as H1N1, Zika, Ebola, and most recently COVID-19. [2][3][4][5][6][7][8][9] While health educators are focused on promoting healthy communities, this is also directly linked to the resilience of a community in the face of public health crises. 10 The Centers for Disease Control and Prevention's Public Health Emergency Preparedness and Response (PHEP) capabilities provide national preparedness standards to support public health emergency planning at state and local levels.…”
Section: Introductionmentioning
confidence: 99%